Fostering Green Exports through Voluntary Sustainability Standards - United Nations Conference on Trade; Development (United Nations, 2020)
The 2030 Agenda and its Sustainable Development Goals set the world on the path of sustainable development and give international trade an important role to play in this journey: “International trade is an engine for inclusive economic growth and poverty reduction, [which] contributes to the promotion of sustainable development” (Paragraph 68, the 2030 Agenda for Sustainable Development) How can international trade become a driving force for a development as sustainable as it is inclusive, ensuring that no one is left behind? How can it respond to the growing demand for production, exchange and consumption patterns that are both environmentally and socially sustainable, as well as economically profitable? To help developing countries build their capacity to achieve sustainable and inclusive growth through trade, the United Nations Conference on Trade and Development (UNCTAD) has examined ways for fostering green exports via the exploitation of voluntary sustainability standards (VSS). VSS are norms and standards to ensure that a product is produced, processed or transported sustainably in terms of, e.g. respect for human rights, decent working conditions, gender equality or environmental protection, with a view to achieving environmental, social and economic objectives. Certification is one of the many VSS tools used by producers and organic standard is the most widely applied VSS in the agricultural sector. To this end, UNCTAD has worked with three countries in the Asia-Pacific Region (Lao PDR, the Philippines and Vanuatu) and developed an approach, which is ready-to-use, streamlined and adaptable to local specificities.This portfolio presents the main outcomes of this development account project, including the approach and tools developed in its framework:• An introduction to green exports and VSS: opportunities and challenges for developing countries • UNCTAD's approach and tools to build countries' capacity to foster green exports through VSS • The country case study of Vanuatu • The country case study of the Philippines • The country case study of Lao People's Democratic Republic